Characterizing Mobilized Virulence Factors and Multidrug Resistance Genes in Carbapenemase-Producing Klebsiella pneumoniae in a Sri Lankan Hospital - Zhu, Chendi; Liyanapathirana, Veranja; Li, Carmen; Pinto, Vasanthi; Hui, Mamie; Lo, Norman; Wong, Kam T.; Dissanayake, Nilanthi; Ip, Margaret (Frontiers in Microbiology, 2018)
Whole genome sequencing of carbapenem-resistant Enterobacteriaceae from the intensive care units of a Sri Lankan teaching hospital revealed the presence of carbapenemase gene, blaOXA-181 among isolates of carbapenase-producing Klebsiella pneumoniae belonging to ST437 (2 strains) and ST147 (8 strains) in 2015. blaOXA-181 genes were carried in three variants of ColE-type plasmids. Elevated carbapemen resistance were observed in ompK36 mutant strains. ESBL genes, plasmid–mediated quinolone resistance (PMQR) determinants (qnr, aac(6’)-Ib-cr, oqxAB) and mutations on chromosomal quinolone resistance-determining regions (QRDRs) with substitutions at ser83→I of gyrA and ser80→I of parC were observed. All strains obtain yersiniabactin on mobile element ICEkp and other virulence determinants. Strict infection control and judicious use of antibiotics are warranted to prevent further spread of multidrug-resistant Klebsiella pneumoniae.